CONSTRUCTION OF MOTIVATION IN PARADIGM OF THE ORGANIZATION - N. Tverdola (Вестник университета)
The article reveals the cross-theme. This theme connects the most famous theories of motivation and terminology of international standards of quality management and social responsibility, of management by objectives, of balanced scorecard logically and provides practical guidance for the design of motivations schemes.